BUMDes Management Through Accounting Information Systems at BUMDes in Cisarua District, West Bandung District - Siti Kustinah; Heni Nurani Hartikayanti; Edi Winarso (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2022)
Village-Owned Enterprises were formed to improve the financial capacity of the village government in administering government and increasing community income through various economic business activities in rural communities. However, in reality, the goal of establishing a BUMDes in the Cisarua District has not been fully achieved. The understanding of BUMDes managers on the importance of BUMDes management, especially regarding the BUMDes accounting system, has not been fully implemented optimally. Socialization about the importance of professional BUMDes management through applying the accounting system is one alternative solution to solve this problem. Through the socialization program that has been carried out, the results obtained are that there is a fairly good understanding of the BUMDes managers in several things that need to be addressed in professional BUMDes management, namely the participants' understanding of the elements of professional BUMDes management and participants' understanding of the need for information technology. In contrast, the understanding of Village Owned Enterprises managers in Cisarua District, West Bandung Regency regarding accounting information systems showed poor results, especially participants' understanding of the accounting system, financial statements, especially equity reports and cash flow statements.